2020
DOI: 10.33086/ijmlst.v2i1.1467
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity Assay Using Brine Shrimp Lethality Test on Collagen-Chitosan Wond Dressing Sterilized by Ultraviolet Light

Abstract: Collagen gives a moist state on the wound area to accelerate the wound healing process. Chitosan is a polymer as known as non-toxic, antibacterial, antifungal, biodegradable, and biocompatible materials. Combination of collagen and chitosan expected to be the  best biomaterials as a wound dressing for the healing process. The study aimed to determine cytotoxicity assay on collagen-chitosan wound dressing  sterilized by ultraviolet (UV) Light using Brine Shrimp Lethality Test (BSLT) method. The test groups were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
4
0
2
Order By: Relevance
“…UV exposure on composites is able to maintain material sterility. 4 UV spectrum divided into UVA with a wavelength of 400 nm to 315 nm, UVB with 315 nm to 280 nm, and UVC with 280 nm to 200 nm. UVC 32 , UV spectrum entirely could inhibit or inactivation of microorganisms, but based on Martin et al (2008) showed UVC with 265 nm was an optimum wavelength as being the most germicidal effect.…”
Section: Original Articlementioning
confidence: 99%
See 2 more Smart Citations
“…UV exposure on composites is able to maintain material sterility. 4 UV spectrum divided into UVA with a wavelength of 400 nm to 315 nm, UVB with 315 nm to 280 nm, and UVC with 280 nm to 200 nm. UVC 32 , UV spectrum entirely could inhibit or inactivation of microorganisms, but based on Martin et al (2008) showed UVC with 265 nm was an optimum wavelength as being the most germicidal effect.…”
Section: Original Articlementioning
confidence: 99%
“…Wound dressing is categorized into traditional dressing including cotton wool, bandages, plasters, lint's, gauzes, and modern wound dressing including foams, composites, films, hydrogels hydrocolloids. 1,2, 4 Selected biomaterial should be considered as a component wound dressing to ensure wound healing gong faster. Collagen and chitosan are known as excellent biomaterial to produce a various biomedical application.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BSLT sering digunakan sebagai uji pendahuluan/ praskrining aktivtas biologis yang sederhana untuk menentukan toksisitas suatu senyawa dari sampel dengan menggunakan hewan uji larva udang (A. salina Leach.). Hasil yang diperoleh dihitung sebagai nilai LC₅₀ (Lethal Concentration), yaitu jumlah konsentrasi ekstrak uji yang dapat menyebabkan kematian larva udang sejumlah 50% setelah masa inkubasi 24 jam (29). Nilai LC₅₀ >1000 ppm dikategorikan tidak beracun (30).…”
Section: Gambar 1 Kromatogram Senyawa Hasil Lc-ms Terhadap Waktu Rete...unclassified
“…Судалгаанд авсан цайраар Авгалдай үүсэж буй II-р шатанд 10 авгалдайг авч 5 мл далайн ус агуулсан петрийн аяганд хийсний дараа шинжилж буй дээжнээс 0.5 мл (10-4000 ppm) нэмж, тасалгааны температурт 24 цаг ажиглана. 24 цагийн хугацаанд үхсэн болон амьд үлдсэн авгалдайн тоог тоолж, дараах томьёогоор хоруу чанарыг тодорхойлно[18][19][20]. Гарган авсан цайраар баяжуулсан гидролизатын ерөнхий үзүүлэлтүүд болох уураг, амины азот, тос, чийг, үнс, азот уусалтын индекс зэргийг тодорхойлон, дүнг Хүснэгт 2-д үзүүлэв.…”
unclassified